2014
DOI: 10.1371/journal.pone.0094987
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Biological Determinations of Meningioma Progression and Recurrence

Abstract: Meningiomas are tumors that arise from the coverings of the brain or spinal cord. 5% of the cases turn into malignant forms with aggressive clinical behavior and increased risk of tumor recurrence. One hundred and five patients with meningiomas were operated by open surgery. To investigate predictors of meningioma recurrence in total 124 samples of 105 patients were investigated by iFISH. Dual-probe hybridization was performed to access chromosomal alterations of chromosomes 1p-, 9p- and 22q. Additionally, met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 47 publications
2
59
1
Order By: Relevance
“…In fact, no significant difference in recurrence time was observed between patients with and without loss of 22q. 30,31 Conversely, the association between prognosis and mutations of TRAF7, AKT1, KLF4, and SMO, called the TRAKLS type in this study, have never been investigated. Here we revealed that genotype was associated with recurrence independently from the degree of surgical resection completeness (Simpson grade) and histological malignancy (Ki-67 LI and WHO grade), which is known as prognostic factors in meningioma.…”
Section: Discussionmentioning
confidence: 87%
“…In fact, no significant difference in recurrence time was observed between patients with and without loss of 22q. 30,31 Conversely, the association between prognosis and mutations of TRAF7, AKT1, KLF4, and SMO, called the TRAKLS type in this study, have never been investigated. Here we revealed that genotype was associated with recurrence independently from the degree of surgical resection completeness (Simpson grade) and histological malignancy (Ki-67 LI and WHO grade), which is known as prognostic factors in meningioma.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast to intracranial tumors, gender and age do not influence prognosis. It is noteworthy that features associated with an increased rate of recurrence in CNS meningiomas (increased mitotic activity, loss of architectural pattern, hypervascularity, necrosis, spindle cell formation, nuclear pleomorphism) [77,[83][84][85] are rarely found in sinonasal tract tumors, and when present, are not associated with a worse outcome. If there is death with tumor, it is usually due to involvement of the vital structures of the mid-facial region or to complications of the surgery, rather than to the aggressive nature of the tumor.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Abnormalities in genes on chromosomes 1p, 6, 9p, 10q, 14q, 17p, 18q and 22 have been described, [77,84,87,88] with deletions of chromosome 22 (monosomy 22) the most consistent cytogenetic alteration. Specifically, these include mutations of the NF2 gene (chromosome 22q12.2), which codes for the protein merlin, a tumor suppressor gene.…”
Section: Ancillary Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the difficulty of managing meningioma recurrence (2) and the low predictive powers of clinic pathological factors, biomarkers to identify high-risk patients with a poor prognosis are strongly needed. From a previous study conducted in a total 124 samples from 105 patients using the high-resolution FISH-technology (iFISH), it is reported that the deletion of chromosome 1p may be an independent marker of meningioma recurrence and progression (3).…”
Section: Introductionmentioning
confidence: 99%